Defining Global Benchmarks in Elective Secondary Bariatric Surgery Comprising Conversional, Revisional, and Reversal Procedures. Issue 5 (November 2021) - Gero, Daniel; Vannijvel, Marie; Okkema, Sietske; Deleus, Ellen; Lloyd, Aaron; Lo Menzo, Emanuele; Tadros, George; Raguz, Ivana; San Martin, Andres; Kraljević, Marko; Mantziari, Styliani; Frey, Sebastien; et al.
Abstract : Objective: To define "best possible" outcomes for secondary bariatric surgery (BS). Background: Management of poor response and of long-term complications after BS is complex and under-investigated. Indications and types of reoperations vary widely and postoperative complication rates are higher compared to primary BS. Methods: Out of 44, 884 BS performed in 18 high-volume centers from 4 continents between 06/2013-05/2019, 5, 349 (12%) secondary BS cases were identified. Twenty-one outcome benchmarks were established in low-risk patients, defined as the 75th percentile of the median outcome values of centers. Benchmark cases had no previous laparotomy, diabetes, sleep apnea, cardiopathy, renal insufficiency, inflammatory bowel disease, immunosuppression, thromboembolic events, BMI> 50 kg/m 2 or age> 65 years. Results: The benchmark cohort included 3143 cases, mainly females (85%), aged 43.8 ± 10 years, 8.4 ± 5.3 years after primary BS, with a BMI 35.2 ± 7 kg/m 2 . Main indications were insufficient weight loss (43%) and gastro-esophageal reflux disease/dysphagia (25%). 90-days postoperatively, 14.6% of benchmark patients presented ≥1 complication, mortality was 0.06% (n = 2). Significantly higher morbidity was observed in non-benchmark cases (OR 1.37) and after conversional/reversal or revisional procedures with gastrointestinal suture/stapling (OR 1.84). Benchmark cutoffs for conversional BS were ⩽4.5% re-intervention, ⩽8.3% re-operation 90-days postoperatively. At 2-years (IQR 1–3) 15.6% of benchmark patients required a reoperation. Conclusion: Secondary BS is safe, although postoperative morbidity exceeds the established benchmarks for primary BS. The excess morbidity is due to an increased risk of gastrointestinal leakage and higher need for intensive care. The considerable rate of tertiary BS warrants expertise and future research to optimize the management of non-success after BS. Abstract : Supplemental Digital Content is available in the text